1997
DOI: 10.1002/(sici)1097-0215(19970207)70:4<390::aid-ijc3>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Ki-ras, p53 andAPC genes in adenocarcinomas of the human small intestine

Abstract: In contrast to the origins of colorectal carcinomas, the mechanisms of carcinogenesis in the small intestine remain unclear. We therefore analyzed the mutational status of the Ki-ras, p53, and adenomatous polyposis coli (APC) genes in primary carcinomas of the small intestine and compared the mutation patterns with those established for colorectal cancers. DNA was extracted from 15 formalin-fixed, paraffinembedded lesions. Codons 12, 13 and 61 of the Ki-ras gene, exons 5-8 of the p53 gene, and codons 1268-1569… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 13 publications
4
14
0
Order By: Relevance
“…The wild type sequence is given in the upper row, the mutated sequence in the lower row other chromosomes (4q, 6q, 8p, 15q). Thus, con®rming previous data (Rashid and Hamilton, 1997, Arai et al, 1997) the presently investigated sporadic carcinomas lack evidence of a signi®cant role of APC inactivation in their development. This is intriguing because the elevated risk of small intestinal carcinomas in patients with familial adenomatous polyposis and the high incidence of small intestinal tumours in mice with germline APC mutations (Moser et al, 1990) suggest a role of APC in the maintenance of regular cell growth in the small intestine.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The wild type sequence is given in the upper row, the mutated sequence in the lower row other chromosomes (4q, 6q, 8p, 15q). Thus, con®rming previous data (Rashid and Hamilton, 1997, Arai et al, 1997) the presently investigated sporadic carcinomas lack evidence of a signi®cant role of APC inactivation in their development. This is intriguing because the elevated risk of small intestinal carcinomas in patients with familial adenomatous polyposis and the high incidence of small intestinal tumours in mice with germline APC mutations (Moser et al, 1990) suggest a role of APC in the maintenance of regular cell growth in the small intestine.…”
Section: Discussionsupporting
confidence: 85%
“…By microsatellite analysis they have found low frequencies of deletions at chromosomal arms 5q, the location of the APC gene, and at 18q, where the DCC-, and DPC4/SMAD4 genes are located. The frequency of replication errors, k-ras mutations, and deletions at 17p, the location of the p53 gene, were reported to be similar to the frequency in colorectal carcinomas (Rashid and Hamilton, 1997;Sutter et al, 1996;Arber et al, 2000), while mutational analysis of APC showed infrequent genetic inactivation of this gene in small intestinal carcinomas (Arai et al, 1997).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Nishiyama et al (7) and Arai et al (8) reported that 40–50% of cases of PSBA overexpress the p53 protein, suggesting that p53 may have a major role in the progression of carcinoma of the small bowel (7,8). In the present case, no p53-positive epithelial cells were found in the normal mucosa; however, p53-expressing cells were observed in the adenoma tissue and the level of p53 expression and the number of p53-expressing cells was higher in the adenocarcinoma tissue, consistent with previous findings (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…This hyperproliferative mucosa then undergoes additional genetic ''hits'' that eventually result in malignant transformation, and ultimately tumor invasion and metastasis [6]. Despite the understanding gained from min mouse model, APC mutations in human SBA are actually uncommon [7]. Other mutations found to occur include abnormalities in the K-ras and p53 genes, though the frequency of abnormalities in the p53 gene is much lower than that observed in human colon cancer [8].…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%